Acción inhibitoria del probiótico bifidobacterium breve sobre lactobacillus acidophilus y revisión de la literatura del efecto inhibitorio de lactobacillus rhamnosus sobre lactobacillus spp - Castro Pieruccini, Braian Emmanuel (Universidad Antonio Nariño, 2021)
Probiotics have been beneficial to health. Today they are used to balance bacterial flora avoiding many sicknesses. They are implemented in the oral cavity to inhibit microorganisms that cause dental cavities avoiding one of the most prevalent sicknesses on planet earth. OBJECTIVE: Determine the inhibitory action of probiotic Bifidobcterium breve over Lactobacillus acidophilus and determine the effect through bibliographic revision of Lactobacillus rhamnosus over Lactobacillus spp. METHODS AND MATERIALS: The purpose of this study was based on determining the inhibitory effect of the probiotics Bifidobacterium breve over Lactobacillus acidophilus, in an in vitro study cultivated in petri boxes inoculated with L. acidophilus in a massive form, they were inoculated in the center with B. breve to observe the inhibitory effect of this last one over L. acidophilus, measuring a halo of inhibition. Variables that were evaluated had, inhibitory effect of Lactobacillus and Bifidobacterium spp. over L. acidophilus, determined by a halo of inhibition (mm) formed around each probiotic colony. It was complemented with a qualitive documental study based on a revision of literature to determine the inhibitory effect of Lactobacillus rhamnosus over Lactobacillus spp. RESULTS: It’s determined that Bifiobacterium breve has inhibitory effect over Lactobacillus acidophilus, a revision of literature from different scientific studies revealed that Lactobacillus rhamnosus has an inhibitory effect over Lactobacillus spp. CONCLUSION: It’s determined that there exists an inhibitory effect of Bifidobacterium breve over Lactobacillus acidophilus. Determined by a bibliographic revision that Lactobacillus rhamnosus has inhibitory effect over Lactobacillus spp.